2003
DOI: 10.3390/s30100001
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Detection of Antioxidative Properties of Flavonoids Using Electrically Heated DNA Modified Carbon Paste Electrode

Abstract: Abstract:A simple electrochemical sensor consisting of electrically heated carbon paste electrode with the surface modified by dsDNA is used to characterize voltammetric behaviour and antioxidative activity of four selected flavonoids. Quercetin, rutin, catechin and epigallocatechin gallate accumulate within the DNA layer. A positive effect of the electrode temperature within the range of 20 to 38 ºC on the detection of a deep DNA degradation by a copper(II)/H 2 O 2 /ascorbic acid cleavage mixture as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Many techniques including spectrophotometry [6][7][8], capillary electrophoresis [9,10] and electrochemical [11][12][13][14] measurement have been employed for the determination of this antioxidant. The spectrophotometric method has been widely used for individual and simultaneous determination of rutin and other flavonoids [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques including spectrophotometry [6][7][8], capillary electrophoresis [9,10] and electrochemical [11][12][13][14] measurement have been employed for the determination of this antioxidant. The spectrophotometric method has been widely used for individual and simultaneous determination of rutin and other flavonoids [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some studies showed the electrochemistry [29][30][31][32][33][34] of flavonoids, including quercetin and kaempferol, as well as the relation between the oxidation potentials and the anti-oxidant activity [35]. Cyclic voltammetry (CV) has been commonly used in these studies [21,[29][30][31][32] to evaluate and identify oxidation peaks, while only in [28] this information was obtained by square-wave voltammetry (SWV) and in [36,37] by differential pulse voltammetry (DPV).…”
Section: Introductionmentioning
confidence: 99%
“…194e467 mV. This peak can be associated to the flavonoid acids which possess easily oxidable orto-diphenol groups (El-Hady & El-Maali, 2008;Korbut, Buckova, Labuda, & Grundler, 2003). Such compounds include caffeic acid, gallic acid, tannic acid, catechin, etc (Bamforth, 2004(Bamforth, , 2006 2010).…”
Section: Resultsmentioning
confidence: 99%